Urinary tract infections and antimicrobial susceptibility pattern among female students in a tertiary institution in South West Nigeria. (2020)
Background: Urinary tract infections (UTIs) is a common medical problem that affects all age groups but with significant morbidity in females because of the nature of their anatomy and physiology. This study was aimed to identify the common causative organisms of UTI and their antimicrobial susceptibility pattern among female students in Babcock University. Methods: A cross sectional study, in which 200 female participants with symptoms of UTI were recruited. Mid stream urine was collected from them and processed using the standard microbiological procedures. Antimicrobial susceptibility testing was performed on isolates from the samples with significant bacteriuria. Socio-demographic and risk factors were obtained using standard questionnaires, and statistical analysis was performed using SPSS version 23.0. Results: UTIs were confirmed in 14.5% (29/200) participants. Of the pathogens isolated, Escherichia coli was predominant 30.6% (11/36). Most of the pathogens isolated were susceptible to ofloxacin and gentamicin, while ceftriaxone had the least susceptibility (18.2%). The majority of the participants, 165 (82.5%) though symptomatic, did not have bacteriuria. The participants aged 15–20 years were mostly infected [24 (13.4%)]. No significant association was found between the socio-demographic factors and UTI. Conclusion: The prevalence of UTI from this study was 14.5%. E. coli was the predominant bacteria pathogen isolated, and of loxacin and gentamycin were the most active antibiotics on susceptibility pattern. The majority of the patients though symptomatic, had no pathogens isolated from their urine. Therefore, caution should be applied on the use of antibiotics when managing UTI based on symptoms alone, to prevent antibiotic resistance.